Hilbert transform in ultrasound medical image detection - Jiang, Chao (2010)
In this project, it starts from a basic study on the medical ultrasound image processing. Then it moves the focus into Hilbert transform study. During the study, it is not only the product theory of Hilbert transform has been explored but also a new solution of envelope detection is discovered based on the product theory. The new solution shows that the envelope of product of two non-overlapping signals is the product between rectification (absolute) of low frequency signal and envelope of high frequency signal. Besides this, the product of two overlapping spectrum signal is explored.